Neutralization of bitis parviocula (Ethiopian mountain adder) venom by the south african institute of medical research (SAIMR) antivenom - Sánchez, Elda E.; Hotle, Doug; Rodríguez-Acosta, Alexis (Revista do Instituto de Medicina Tropical de São Paulo, 2011)
BACKGROUND: The Ethiopian mountain adder (Bitis parviocula) is a viperid known only from a few locations in southwestern Ethiopia. METHODS: a total of 30 µg of B. arietans and B. parviocula venoms were run on a 10-20% Tricine gel. To assay lethality dose fifty (LD50), five groups of eight mice for each venom were used. Hemorrhagic activity for crude venom was tested. Fibrinogenolytic activity of crude venom was measured using (2.5 mg/mL) of fibrinogen solution and (0.03 mg/mL) of crude venom. Gelatinase activity of the venom was tested on a Kodak X-OMAT TM film. Crude venoms of B. parviocula and B. arietans were tested for their abilities to affect clotting time, clotting rate and platelet function on whole human blood. RESULTS: The (SAIMR) antivenom was confirmed in this study to neutralize the lethal activity of venom from Bitis parviocula. The ED50s of SAIMR antivenom on B. parviocula and B. arietans neutralized half of 18.2 and 66.7 mg of venom, respectively. The hemorrhagic activities (MHDs) of B. parviocula and B. arietans were 0.88 and 1.7 µg, respectively. Bitis arietans and B. parviocula venoms degradated α and β chains at different times. The γ chains remained unaffected. Bitis parviocula venom did not exhibit gelatinase activity, while B. arietans had a MGD of 6.9 µg. At 3 mg/mL, the crude venoms of B. parviocula and B. arietans did not significantly affect clotting time or clotting rate. CONCLUSIONS: The SAIMR antivenom is very effective in neutralizing the venom of B. parviocula and should be considered in treating envenomations by these snakes.